The taxonomy and nomenclature associated with Kalanchoe adelae (Crassulaceae subfam. Kalanchooideae) - Smith, Gideon F. (Phytotaxa, 2024)
The taxonomy and nomenclature associated with the name Kalanchoe adelae (Crassulaceae subfam. Kalanchooideae) are discussed and clarified. The only material mentioned by Raymond-Hamet when the name K. adelae was treated in the second part of his two-part monograph of the genus was “M. [Mr] Humblot, no 1570”. Four specimens collected by Léon Joseph Henry [Henri] Humblot (1852–1914), under his collecting number ‘1570’, all of them syntypes, which were annotated with the name K. adelae, as well as, in det., with the illegitimate name K. floribunda Tulasne, non Wight & Walker-Arnot, for that matter, are held at Herb. P. An attempted re-typification of the name K. adelae by Bernard Descoings in 2003 on material collected by [Mr Louis-Hyacinthe] Boivin (1808–1852) was not effective.